2017
DOI: 10.24925/turjaf.v5i5.471-475.927
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Nutrient Management on Soil Properties and Nutrient Uptake by Red Onion

Abstract: to study the impact of Integrated Nutrient Management on some soil properties and nutrients uptake by red onion (Allium cepa L.) in Moda, Michika, Adamawa state, Nigeria. Soil samples were randomly collected and analysed for pH, EC, organic carbon, organic matter, total nitrogen, available phosphorus before and at the completion of the experiment. Total nitrogen, phosphorus and potassium contents of the onion bulbs were determined. There was an improvement in the fertility status of the soil as a consequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Mafongoya and Jiri (2016) reported that chemical fertilizer plus manure increased bulb yield from 43.2 t ha -1 to 85.2 t ha -1 . Kwaghe et al (2017) also reported that NPK + poultry manure gave a higher bulb yield than NPK fertilizer alone. The addition of organic material increased the bulb yield due to the increasing micronutrients and soil pH.…”
Section: Bulb Yieldmentioning
confidence: 94%
“…Mafongoya and Jiri (2016) reported that chemical fertilizer plus manure increased bulb yield from 43.2 t ha -1 to 85.2 t ha -1 . Kwaghe et al (2017) also reported that NPK + poultry manure gave a higher bulb yield than NPK fertilizer alone. The addition of organic material increased the bulb yield due to the increasing micronutrients and soil pH.…”
Section: Bulb Yieldmentioning
confidence: 94%
“…This is in accordance with the opinion of Aboukhadrah et al, (2017), the response of plants to fertilization will increase if the application of fertilizer is in accordance with the time, and the right way. The results of Kwaghe et al, (2017), showed that the addition of compost up to a dose of 20 tons / ha did not affect the growth of plant height, stem diameter, leaf area index and number of leaves per plant.…”
Section: Number Of Leaves (Fruit)mentioning
confidence: 94%